2015
DOI: 10.1038/leu.2015.288
|View full text |Cite
|
Sign up to set email alerts
|

Complex molecular genetic abnormalities involving three or more genetic mutations are important prognostic factors for acute myeloid leukemia

Abstract: We conducted a comprehensive analysis of 28 recurrently mutated genes in acute myeloid leukemia (AML) in 271 patients with de novo AML. Co-mutations were frequently detected in the intermediate cytogenetic risk group, at an average of 2.76 co-mutations per patient. When assessing the prognostic impact of these co-mutations in the intermediate cytogenetic risk group, overall survival (OS) was found to be significantly shorter (P=0.0006) and cumulative incidence of relapse (CIR) significantly higher (P=0.0052) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
4
36
1
1
Order By: Relevance
“…16,17 These findings suggest that cases with a large number of gene mutations have a correspondingly high level of genomic instability and point to the strong possibility of mutations in genes not yet examined. 34 This is thought to result in a poorer prognosis. Our finding that prognosis in AML worsens with increasing number of DMRGM suggests that to improve prognostic analysis in AML it will be important not only to focus on each individual gene mutation, but also to seek to identify overall genomic instability in individual cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 These findings suggest that cases with a large number of gene mutations have a correspondingly high level of genomic instability and point to the strong possibility of mutations in genes not yet examined. 34 This is thought to result in a poorer prognosis. Our finding that prognosis in AML worsens with increasing number of DMRGM suggests that to improve prognostic analysis in AML it will be important not only to focus on each individual gene mutation, but also to seek to identify overall genomic instability in individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…33 We have also reported recently that three or more gene mutations is an unfavorable prognostic factor in de novo AML. 34 According to whole-exon mutation analysis using a next-generation sequencer, there are on average 2.5-5.0 gene mutations per case in AML, 14,18,34 and it has been established that the onset of AML requires the combination of a number of gene mutations. 16,17 These findings suggest that cases with a large number of gene mutations have a correspondingly high level of genomic instability and point to the strong possibility of mutations in genes not yet examined.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of a mutation such as DNMT3A may occur even in clinical remission 43 as would be expected since DNMT3A mutations may be present in normal individuals 42 . Earlier, an analysis of 18 genes in a study of 398 AML patients less than 60 years of age had suggested that mutational profiling could potentially be used for risk stratification, with internal tandem duplication in FLT3 (FLT3-ITD), partial tandem duplication in MLL (MLL-PTD) and mutations in ASXL1 associated with reduced overall survival, while CEBPA and IDH2 mutations were associated with improved survival 44 . Only the IDH2 R140Q mutations had a favorable effect in these patients 44 .…”
Section: Mutations In Pathogenesis Of Amlmentioning
confidence: 99%
“…Earlier, an analysis of 18 genes in a study of 398 AML patients less than 60 years of age had suggested that mutational profiling could potentially be used for risk stratification, with internal tandem duplication in FLT3 (FLT3-ITD), partial tandem duplication in MLL (MLL-PTD) and mutations in ASXL1 associated with reduced overall survival, while CEBPA and IDH2 mutations were associated with improved survival 44 . Only the IDH2 R140Q mutations had a favorable effect in these patients 44 . Recently, in a study of 28 recurrently mutated genes in 271 patients with de novo AML, complex molecular genetic abnormalities involving three or more genetic mutations were found to be a strong independent prognostic factor, even among patients <65 years of age who were also negative for FLT3-ITD 45 .…”
Section: Mutations In Pathogenesis Of Amlmentioning
confidence: 99%
See 1 more Smart Citation